Impact of Gender and Ethnic Composition of South African Boards of Directors on Intellectual Capital Performance - Van der Zahn, Jean-Luc Wolfgang Mitchell (Institutional Knowledge at Singapore Management University, 2006)
This study examines the association between the gender and ethnic composition of boards of directors and firm performance in a transitional nation. In contrast to prior research that largely focuses on firm performance within a financial context, this study concentrates on intellectual capital performance. Using data collected from 84 South African, empirical results indicate a positive association between the percentage of female and non-white directors on the board and a firm’s intellectual capital performance. Additional analysis shows the designation of female directors as an insider has a negative effect of intellectual capital performance. Designation of female and non-white directors as outsiders, meanwhile, has a positive influence on a firm’s intellectual capital performance. Finally, there was no association between the percentage of non-white inside directors on the board and intellectual capital performance.